A randomized clinical trial of Cogmed Working Memory Training in school‐age children with ADHD: a replication in a diverse sample using a control condition. (7th October 2013) - Chacko, A.; Bedard, A.C.; Marks, D.J.; Feirsen, N.; Uderman, J.Z.; Chimiklis, A.; Rajwan, E.; Cornwell, M.; Anderson, L.; Zwilling, A.; Ramon, M.
<x xml:space="preserve">Abstract</x> Background Cogmed Working Memory Training (CWMT) has received considerable attention as a promising intervention for the treatment of Attention‐Deficit/Hyperactivity Disorder (ADHD) in children. At the same time, methodological weaknesses in previous clinical trials call into question reported efficacy of CWMT. In particular, lack of equivalence in key aspects of CWMT (i.e., contingent reinforcement, time‐on‐task with computer training, parent–child interactions, supportive coaching) between CWMT and placebo versions of CWMT used in previous trials may account for the beneficial outcomes favoring CWMT. Methods Eighty‐five 7‐ to 11‐year old school‐age children with ADHD (66 male; 78%) were randomized to either standard CWMT (CWMT Active) or a well‐controlled CWMT placebo condition (CWMT Placebo) and evaluated before and 3 weeks after treatment. Dependent measures included parent and teacher ratings of ADHD symptoms; objective measures of attention, activity level, and impulsivity; and psychometric indices of working memory and academic achievement (Clinical trial title: Combined cognitive remediation and behavioral intervention for the treatment of Attention‐Deficit/Hyperactivity Disorder; http://clinicaltrials.gov/ct2/show/NCT01137318). Results CWMT Active participants demonstrated significantly greater improvements in verbal and nonverbal working memory storage, but evidenced no discernible gains in working memory storage plus processing/manipulation. In addition, no treatment group differences were observed for any other outcome measures. Conclusions When a more rigorous comparison condition is utilized, CWMT demonstrates effects on certain aspects of working memory in children with ADHD; however, CWMT does not appear to foster treatment generalization to other domains of functioning. As such, CWMT should not be considered a viable treatment for children with ADHD.